2018
DOI: 10.3892/ijmm.2018.4001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of SMAD3 is critical in�osteoblast differentiation of PDMCs

Abstract: Human pluripotent stem cells have the potential assist in the identification of genes involved in mammalian development. The human placenta is considered a repository of stem cells, termed placenta-derived multipotent cells (PDMCs), which are able to differentiate into cells with an osteoblastic phenotype. This plasticity of PDMCs maybe applied clinically to the understanding of osteogenesis and osteoporosis. In the presentstudy, osteoblasts were generated by culturing PDMCs in osteogenic medium. Reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…In agreement with our observation, BMP2 was shown to activate SMAD3-dependent signaling (Ongaro et al, 2019). Transcription factor SMAD3 expression is crucial for osteogenesis and the skeletal development process (Lin et al, 2019). Some studies have demonstrated that TGF-β3 also recruits endogenous human MSCs to initiate bone regeneration.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with our observation, BMP2 was shown to activate SMAD3-dependent signaling (Ongaro et al, 2019). Transcription factor SMAD3 expression is crucial for osteogenesis and the skeletal development process (Lin et al, 2019). Some studies have demonstrated that TGF-β3 also recruits endogenous human MSCs to initiate bone regeneration.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Borton et al revealed that Smad3 knockout mice had osteopenia after weaning [23]. Additionally, Smad3 can also participate in the proliferation and osteogenic differentiation of BMSCs [24]. Previous studies have suggested that lncRNA H19 can promote BMSC osteogenic differentiation, which is related to Smad3 [25].…”
mentioning
confidence: 99%
“…As illustrated in Fig. 5A , the key TFs that have been widely proved to be involved in osteogenesis ( SMAD3 [ 43 ], FOXO1 [ 44 ], SOX4 [ 45 ]) and adipogenesis ( PPARG [ 46 ], EBF1 [ 47 ], CEBPB [ 48 ]) were specifically enriched in osteoblasts-selective and adipocytes-selective SEs sets, respectively, suggesting the vital roles of master TFs in the establishment of SEs. Notably, among these enriched TFs, four TFs ( FLI1 and ETS1 for osteoblasts, NFIL3 and RXRA for adipocytes) were also regulated by lineage-selective SEs (Fig.…”
Section: Resultsmentioning
confidence: 99%